“Prosumage” and the British electricity market - Green,RJ; Staffell,IL (Economics of Energy and Environmental Policy, 2017)
Domestic electricity consumers with PV panels have become known as “prosumers”; some of them also have energy storage and we have named the combination “prosumage”. The challenges of renewable intermittency could be offset by storing power, and many engineering studies consider the role and value of storage which is properly integrated into the ‘smart grid’. Such a system with holistic optimal control may fail to materialise for regulatory, economic, or behavioural reasons. We therefore model the impact of naïve prosumage: households which use storage only to maximise self-consumption of PV, with no consideration of the wider system. We find it is neither economicfor arbitrage nor particularly beneficial for shaving peaks and filling troughs in national net demand. The extreme case of renewable self-sufficiency, becoming completely independent of the grid, is still prohibitively expensive in Britain and Germany, and even in a country like Spain with a much better solar resource.